300 - Miller, Frank 1957- (Milwaukie, Or. Dark Horse Books, 2006)
The armies of Persia -- a vast horde greater than any the world has ever known -- are poised to crush Greece, an island of reason and freedom in a sea of madness and tyranny. Standing between Greece and this tidal wave of destruction is a tiny detachment of but three hundred warriors. But these warriors are more than men -- they are Spartans!
"This volume collects issues one through five of the Dark Horse comic-book series 300"--T.p. verso.
Keywords: Leonidas -- King of Sparta -- d. 480 B.C. -- Comic books, strips, etc; Xerxes -- I -- King of Persia -- 519-465 or 4 B.C. -- Comic books, strips, etc; Graphic novels; Greece -- History -- Persian Wars, 500-449 B.C. -- Comic books, strips, etc